Tailoring of Optical and Electrical Properties of Transition Metal Ions-Doped ZnO-Based Diluted Magnetic Semiconductor Nanoparticles - Mukherjee, Subhrajit; Kumar, Shiv; Saha, S.; Basu, Soumen; Chatterjee, S.; Ghosh, A.K. (Asian Journal of Chemistry, 2011)
To tailor the optical and electrical properties, Fe-doped ZnO diluted magnetic semiconductor nanoparticles have been synthesized via surfactant assisted co-precipitation technique. The single phased samples are characterized by X-ray diffraction. The optical absorption has been studied from UV-VIS spectroscopy and the optical band gap has been estimated. The variation of band gap with the doping concentration has been plotted. To study the optical properties, photoluminescence and FTIR spectroscopy have been employed. DC resistivity has been investigated with variation of temperature. Activation energy of the samples has been calculated following the Arrhenius law.